Tegralogy of Fallot: Pro-and post-surgical case study - A. Samik Wahab, A. Samik Wahab (Universitas Gadjah Mada, 1989)
Defects in the ventricular septum with obstruction to right ventricular outflow encompass a wide anatomic, physiologic and clinical spectrum. Large ventricular septal defects occur with pulmonic stenosis that varies from mild to severe to complete (pulmonary atresia). Small ventricular septal defects occur with mild to severe pulmonic stenosis. The most familiar and prevalent combination is tetralogy of Fallot with the incidence of approximately 0.4 to 0.6 per 1000 live births.The following illustrates four cases of Fallots tetralogy with a wide anatomic, physiologic and clinical variations. The first case is a small ventricular septa defect along with severe pulmonic stenosis, the fourth case, however, comprises a large VSD and pulmonary atresia, while in the others the anatomic variations are in between.Hypoxic spells are important aspects of the history in Fallots tetralogy. Spells are an alarming episode that should be treated as an emergency. Knee-chest position, squatting or sitting with legs drawn underneath can afford to relief dyspnea.The best treatment, however, is surgical treatment, indicated in all patients with Fallots tetralogy. The result of this surgical treatment up to now is very satisfactory.Key Wards: tetralogy of Fallot - pulmonic stenosis - ventricular septal defect - pulmonary atresia - bicuspid a pulmonalis